(3QSGdI aj Yed PGJ GdcQSjs - (3GdMejOj, eMeO Hf Ydj, J (B1179 (3g`s
(3ChdgG (B:s
(3fMeOc jG ef jOhQ adcc GdOhGQ deG cGfJ PGJ GdcQSj ef GdBdGJ GdQUOjI cKjQI GdeMUhd hjSjQI GdMUhd heY gPG eJQhcI GdYed Hd efSjI GdCUd aj HjGfgG ef GdeSGFd hGdQSGFd s
(3BNQgG (B:s
(3hHbOQ GdNWGWI aj Gddjd aeG MGPGg Cab GdeTQb Edi QCS GdMed ef CLRGA GdeYOd agh eWGdY GdhbJ hEf TFJ RO GdeGVj ef GdfgGQ Ydi eWGdY GdTQhb aj GdfgGQ heWGdY GdZQhH Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\296s
(3GdCYdGe (B6\296s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs